Image encryption based on chaotic map and dynamic S-box - Hung, Pham Anh; Klomkarn, Kitdakorn; Sooraksa, Pitikhate (My University, 2013)
Dynamic substitution box (S-box) constructed from chaotic map is known as the secure improvement of classic S-box. But the general property '1 to 1' mapping of S-box makes the substitution not flexible. This paper proposes new method for image encryption. We use the key matrix randomization concept to apply on dynamic S-box so that S-box becomes '1 to n' mapping and complexity. First, Chaotic NCA map is applied to generate dynamic S-box which is used for substitution. During substitution phase for each image's value, we apply chaotic Arnold cat map combining chaotic Chen system to shuffle the positions of S-box. After that chaotic Baker map which takes parameter sequence from Gauss map is chosen to perform permutation phase. The experiments show that the secure property of this method gets high efficient from attacks. © 2013 IEEE.
Keywords: Arnold cat map; Baker map; Chaotic system; Chen system; Dynamic S-box; Gauss map; Image encryption; NCA map